Rancang Bangun Alat Pengering Cabai Merah secara Elektrik Berbasis Internet of Things - Muhammad Rizki A; Ilmiyati Rahmy Jasril (MASALIQ, 2025)
This study is motivated by the importance of utilizing the Internet of Things (IoT) to support the control of an electric red chili drying system. The research aims to address the challenges of efficiency, quality stability, and post-harvest system modernization, while also contributing to the national food security agenda through the application of appropriate technology in the agricultural and agro-industrial sectors. The method used was the waterfall model, comprising needs analysis, hardware design, software design, tool fabrication, and testing. Testing was conducted on the LCD function, IoT module, chili drying process, temperature stability, and software performance. The drying process was tested in 16 trials, with results showing that the system operated effectively and efficiently. The initial heating stage recorded temperatures from 30.2°C to 51.1°C within 5–15 minutes; the optimal heating stage showed a slower temperature rise to 56–57°C within 30–35 minutes; the stabilization and temperature control stage maintained 57.8–59.9°C for 40–70 minutes; and the final stage reached 60°C at the 75th minute. The system was able to detect the maximum temperature and stop heating to prevent overheating. It is concluded that the application of IoT in the ESP32 microcontroller-based electric red chili dryer significantly improves time efficiency and product quality compared to conventional methods.